(3GdQO Ydi GdQGaVIs - (3CHh eMeO GdbGSe Hf EHQGgje Hf ESeGYjd GdMSfj GdQSj, GdQSj,J (B246 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Ydi cd MGd RYeJ GdQGaVI Cfg de jcf bQf ef GdbQhf NdG EdG hajgG hUi fHi s
(3BNQgG (B:s
(3hEPG de jcf eeG cGf Hg QShd Gddg Ydi ef NCdag eMJLkG de jcf efgLg YfO ef jDef HGddg efgLkG Je s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B171s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdJhMjO hGdedd hGdfMds